Secondary Orality and the Vatican 2024 Declaration on Human Dignity - Farrell, Thomas J. (New Explorations, 2024)
In “Secondary Orality and the Vatican’s 2024 Declaration on Human Dignity,” I highlight, on the one hand, the mature work of the American Jesuit Renaissance specialist and cultural historian and pioneering media ecology theorist Walter J. Ong (1912-2003; Ph.D. in English, Harvard University, 1955), and, on the other hand, the Vatican’s new 2024 Declaration on human dignity – with some discussion of certain related works by David Brooks and other authors.My favorite scholar is my former teacher at Saint Louis University, the American Jesuit Renaissance specialist and cultural historian and pioneering media ecology theorist Walter J. Ong (1912-2003; Ph.D. in English, Harvard University, 1955). In my adult life (I recently turned 80), I have devoted an enormous amount of time and effort to writing about Ong’s mature work from the early 1950s onward.